Awareness and Acceptability of Pre-Exposure Prophylaxis (PrEP) Among Men Who Have Sex with Men in Kazakhstan: A Mixed Methods Study - Bak, Marieke; Dam, Anke van; Janssens, Rien (Central Asian Journal of Medical Sciences, 2018)
Objectives: Oral pre-exposure prophylaxis (PrEP) is an antiretroviral method of HIV prevention recommended to men who have sex with men (MSM) at high risk of infection. In Kazakhstan, which has one of the fastest growing HIV epidemics globally, PrEP is not currently available. The aim of this study is to explore the possibilities for PrEP initiatives in Kazakhstan by investigating awareness and acceptability of this prevention method among MSM. Methods: This mixed-methods study employs an online survey and qualitative interviews to describe PrEP awareness and acceptability. Results: Less than half (39.8%) of survey participants had heard of PrEP. However, a majority (85.2%) of MSM would possibly or defi nitely use PrEP if it was available. Awareness of PrEP was positively associated with willingness to use PrEP. The main reason to be interested in PrEP was an increased feeling of protection, whereas barriers were related to the idea of taking daily medication and the potential for side effects. Conclusion: PrEP is an essential component of HIV combination prevention. Our fi ndings suggest potential for PrEP programmes among MSM in Kazakhstan and possibly in other Central Asian nations, when taking into account burdens of taking PrEP as well as more structural health policy issues.